Structure of the population of the red mangrove crab Goniopsis cruentata (Latreille, 1803) (Crustacea, Decapoda, Brachyura), on a Brazilian sub- tropical estuarine mangrove. - Cobo, Valter José; Fransozo, Adilson (Revista Biociências, 2020)
G. cruentata is one of the most abundant crabs in South Western Atlantic mangroves, and fill most of the niches provided by these ecosystems. The trophic role of this crab in the ecosystem is wider than reported to sesarmid and ocypodid crabs and plays important role on propagule predation, affecting the mangrove recruitment and community composition. This paper reports some population parameters as size classes frequency distribution, breeding period, sex ratio, molt cycle and recruitment of the G. cruentata in southeastern Brazilian coast. A total of 1,150 crabs was obtained, without mean size meaning difference between sexes. Frequency distribution were bell-shaped and adult crabs were dominant. Ovigerous females were recorded in almost all months. The sex ratio shows no meaning difference from 1:1 ratio. Molt activity was recorded over all sampled period. The frequency of molt on the size classes reveals a larger activity regarded to smallest body sizes. The population of G. cruentata seems to follow the expected standards of the tropical marine crabs. Moreover, some population attributes, as recruitment and breeding period did not match exactly within these standards, suggesting that population regulation is constrained for the local conditions.